Օրբելյան և Պռոշյան իշխանների հանդերձանքը հայ միջնադարյան արվեստում - Ենոքյան, Աշխեն
From the first half of the 13th century, the Ōrbeleans and the Pṛosheans, as skilled military and political figures, rose to prominence in their roles while being the leading princes of the Vayots‘ Dzor canton of the Syunik‘ province. They were also distinguished for their endeavors in church-building and cultural activities. The era of their princely dynasties partially overlapped with the establishment of the Ilkhanate dynasty following the Mongol-Tatar invasions which had a significant influence on the political, economic, and cultural landscape of the country, a transformation that was also evident in the attire worn by Armenian princes during that time. Evidence of the aforementioned can be seen in the relief sculptures depicting the Ōrbelean and Pṛoshean princes on the walls of architectural structures dating back to the 13th-14th centuries in the Vayots‘ Dzor canton. These sculptures portray them in attire with details reminiscent of Mongol leaders. Among these, their princely robes, hats, and crowns stand out prominently. However, amidst these, one can also discern national and traditional elements in their vestments, which are most notably exemplified in the architectural design of the Arates Monastery and to some extent in other monuments. This observation provides insights into the Armenian princely attire of that era, effectively distinguishing between traditional and allogenic elements. С первой половины XIII века в провинции Вайоц дзор области Сюник правили князья Орбеляны и Прошяны – искусныe военно-политическиe деятели, известныe также своей ролью в церковном строительстве и развитии культуры. Период существования их княжеских домов частично совпадает с созданным после монголо-татарских нашествий ильханством, которое имело всестороннее влияние как на политическую и экономическую, так и на культурную жизнь страны, что нашло отражение и в княжеском облачении того времени. Об этом свидетельствуют скульптурные изображения князей Орбелянов и Прошянов на стенах датируемых XIII-XIV веками архитектурных строений провинции Вайоц дзор, где они представлены в облачении, детали которого характерны для одежды монгольских предводителей (княжеские пояса, шапки и другие атрибуты). Вместе с тем в княжеском облачении заметны и национальные, традиционные формы, которые наиболее детально представлены в ктиторской композиции монастыря Аратес, отчасти и в других памятниках. Это дает возможность составить представление об армянском княжеском облачении того времени и четко разграничить традиционные и привнесенные извне элементы.
Keywords: Արվեստ